1983
DOI: 10.1161/01.str.14.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Increased transendothelial channel transport of cerebral capillary endothelium in stroke-prone SHR.

Abstract: Permeability of brain capillaries of stroke-prone spontaneously hypertensive rats (SHRSP) was studied using labelling (horseradish peroxidase) and cytochemical techniques at the cellular level. In the cerebral capillary endothelium the tracer molecules were quickly transported by abundant transendothelial channels which directly connected the capillary lumen to the subendothelial space. Transendothelial channels are abundant and should be postulated as structural formations engaged in the increased transport o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In many cases, these structures appear to be unrelated to macromolecular transport (Bungaard 1987;Frøkjaer-Jensen 1991). Conversely, there is a wealth of ultrastructural evidence from several tissue types under variable experimental conditions that implicates the VTS as a macromolecular transporter mechanism (Simionescu et al 1975;Shivers 1979;Lossinsky et al 1983;Tagami et al 1983;Shivers et al 1984;Noguchi et al 1987;Nag 1990;Wagner and Chen 1991;Ogawa et al 1993;Bendayan and Risio 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, these structures appear to be unrelated to macromolecular transport (Bungaard 1987;Frøkjaer-Jensen 1991). Conversely, there is a wealth of ultrastructural evidence from several tissue types under variable experimental conditions that implicates the VTS as a macromolecular transporter mechanism (Simionescu et al 1975;Shivers 1979;Lossinsky et al 1983;Tagami et al 1983;Shivers et al 1984;Noguchi et al 1987;Nag 1990;Wagner and Chen 1991;Ogawa et al 1993;Bendayan and Risio 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The original description of parajunctional VTS in brain injury (Tagami et al 1983) was subsequently considered by others to represent a possible structural mechanism for inflammatory or tumor cell transport across the BBB (Azzarelli et al 1984;Lossinsky et al 1989aLossinsky et al , 1991. Moreover, since the inner delimiting membrane surfaces of the VTS were shown to label alkaline phosphatase (a BBB-specific enzyme), under conditions of CNS injury (Lossinsky et al 1983), this indicates that the VTS are composed of exoplasmic membranes, i.e., extensions of the EC plasmalemmal surface.…”
Section: Discussionmentioning
confidence: 99%
“…SHRSP have been used extensively to study the mechanism of hypertensive damage in the brain. 83 -86 It has been demonstrated, for example, that one of the earliest changes leading to stroke is breach of the BBB 87 and that the arterioles of SHRSP show hyalinosis, fibrinoid necrosis, small aneurysms adjacent to small infarcts, white matter rarefication, and loss of myelin. 85 Several studies have demonstrated the importance of diet in the etiology of stroke in SHRSP; they developed strokes only if fed a specific low-protein fish meal diet.…”
mentioning
confidence: 99%
“…Afterwards, the infarcted cortices were sectioned into small pieces under a microscope as previously reported. 17 In the control group, we killed rats every 4 weeks from 4 to 52 weeks of age by the perfusion fixation method described. We obtained at least 10 cerebral sections of the anteromedial and occipital cortex since these areas were the predominant sites of stroke in SHRSP.…”
mentioning
confidence: 99%